The Working Alliance in Psychotherapy: Risk, Criticism and Perspectives in the Italian Context - Ciliberti, Rosagemma (Psychiatr Psychol Law, 2016)
This paper investigates which factors inherent to the various forms of psychotherapy are conducive to success and which are not. Particular emphasis is placed on the role of communication between the therapist and the patient, with specific regard to the outcome of treatment. The habitual practices and main problems facing healthcare professionals with regard to information and consent to psychotherapy are analysed in the context of the results of some recent studies of outcomes and processes which support the notion that the factors most frequently associated with successful psychotherapy are cooperation, proper information and a shared commitment to achieving the objectives of treatment.